Brachytherapy next generation: robotic systems - Popescu, Tiberiu; Kacsó, Alex Cristian; Pisla, Doina; Kacsó, Gabriel (Journal of Contemporary Brachytherapy, 2015)
In a field dominated by external beam radiation therapy (EBRT), both the therapeutic and technical possibilities of brachytherapy (BT) are underrated, shadowed by protons and intensity modulated radiotherapy. Decreasing expertise and indications, as well as increasing lack of specific BT training for radiation therapy (RT) residents led to the real need of shortening its learning curve and making it more popular. Developing robotic BT devices can be a way to mitigate the above issues. There are many teams working at custom-made robotic BT platforms to perfect and overcome the limitations of the existing systems. This paper provides a picture of the current state-of-the-art in robotic assisted BT, as it also conveys the author’s solution to the problem, a parallel robot that uses CT-guidance.